Transplanting Chapter 11 of the US Bankruptcy Code into Singapore's restructuring and insolvency laws: opportunities and challenges. Issue 1 (2nd January 2019) - McCormack, Gerard; Wan, Wai Yee
ABSTRACT: In 2017, Singapore introduced wide-ranging reforms to its insolvency and restructuring laws with a view to enhancing its attractiveness as an international centre for debt restructuring. Central to these reforms is the transplantation (with modification) of certain provisions from Chapter 11 of the US Bankruptcy Code including the automatic moratorium, cross-creditor cram-down, rescue financing and prepacks. Drawing upon the US experience and similar reform proposals in the EU (including the UK), we critically evaluate the impact of the new Singapore law. We argue that there remain challenges in ensuring that the transplantation works well and highlight the possible unintended consequences of such transplantation.